1991
DOI: 10.1002/jso.2930470309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of splenectomy on pulmonary metastasis and growth of SC42 carcinoma transplanted into mouse liver

Abstract: The carcinoma SC42 was transplanted into the liver of its syngeneic mice DS, and the immunological integrity of the spleen and the effects of splenectomy on the growth and pulmonary metastasis of the liver tumor were assessed. On day 7 after liver tumor transplantation, the natural killer (NK) activity of the splenocytes was significantly elevated; it subsequently decreased at a later stage of the tumor. The response of the splenocytes to PHA and Con-A decreased significantly from the early stage of the tumor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…The experiments of our study provide clear evidence for a division of labor among NK-cell subsets and demonstrate that incomplete NK-cell differentiation observed in Txb21-deficient mice may lead to a deficit in effector antitumoral NK-cell subsets. Furthermore, our findings may also explain the increased NK cell-dependent incidence of pulmonary 45 and hepatic 46 metastasis reported in splenectomized mice.…”
Section: Discussionsupporting
confidence: 52%
“…The experiments of our study provide clear evidence for a division of labor among NK-cell subsets and demonstrate that incomplete NK-cell differentiation observed in Txb21-deficient mice may lead to a deficit in effector antitumoral NK-cell subsets. Furthermore, our findings may also explain the increased NK cell-dependent incidence of pulmonary 45 and hepatic 46 metastasis reported in splenectomized mice.…”
Section: Discussionsupporting
confidence: 52%
“…One of the possible mechanisms is that the activity of natural killer (NK) cells can decrease after splenectomy. Imai et al reported the number of pulmonary metastases in splenectomized mice was significantly greater than in the control group and they suggested that splenic NK cells play an important role in the suppression of pulmonary metastasis in the mouse liver tumor model (17).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic activity of splenocytes was tested in a standard 4-hour 51 Cr release assay, as described previously [25]. Cytotoxicity was assessed against the Yac-1 cell line as an NK target and Meth-A cells.…”
Section: Methodsmentioning
confidence: 99%
“…For depletion of T cells, mice were injected intravenously with 40 µg of anti-thy 1,2 (CD90) mAb (Cedarlane), anti-CD4 mAb (clone H129.19, rat IgG2a; PharMingen, San Diego, Calif., USA) or anti-CD8 mAb (clone 53-6.7, rat IgG2a; PharMingen), and for depletion for NK cells, 100 µl of anti-asialo GM1 antiserum (Wako Pure Chemical Industries Ltd., Osaka, Japan) diluted at 10/1 was injected into each mouse through the caudal vein, 1 day before tumor cell injection, according to the manufacturer’s instructions and previously published methods [25, 26, 27, 28]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation